Analysis of customer profitability and its role in managing the relationship with the customer to improve sustainable competitive advantage: an applied comparative study between the traditional costing approach and the activity-based costing approach in I - Mohammed wafi Abbas; Abwalhsnyn Muhsin Jawda (Iraqi Journal for Administrative Sciences, 2025)
This research is an attempt to find resolution for the study problem represented by that the cost traditional system of the current economical units does not show the customer profitability analysis; if an accountant attempt to conduct such analysis the result would be misleading information due to depending on obscure data relating the indirect cost, and this would resulted in making wrong decisions. The study aims basically to analyze the customer profitability according to the traditional method and the cost method basing on activities. The two method are compared with each other to show the role of each one in managing the costumer relation and the competitive advantage of the economical unit. To achieve this aim, the research depends on the following hypothesis( using the customer profitability analysis according to the cost method basing on activities would provide the information that help the administration in improving its relation with the costumer, and consequently, achieve the sustainable competitive advantage. The research concludes a number of theoretical and practical conclusions; the most important one is that analyzing customer profitability according to the traditional system of costs has a negative effect on managing the costumer relation and the competitive advantage as it give misleading information and data due to depending on obscure data relating the indirect cost, and this would resulted in making wrong strategic decisions. The researcher recommends the following:- To apply customer profitability analysis, the economical units have to provide all the required devices and means, designing the records and documents to provide detailed information represented by the revenues and costs on the level of costumer.